(untitled) (Stato, Chiese e pluralismo confessionale, 2025)
Il “dovere del digiuno”. Astinenza dal cibo e sicurezza alimentare Despite the universal declaration of the right to food, global hunger remains a persistent crisis. Paradoxically, many of the world’s major religions incorporate fasting as a central practice, seemingly at odds with the fundamental need for sustenance. This essay explores this apparent contradiction, focusing on major religious traditions to examine the nuanced relationship between the right to food and the duty of fast. It argues that religious fasting, far from undermining food security, can cultivate values such as self-restraint, communal responsibility, and empathy for the hungry, indirectly supporting efforts to ensure more equitable access to food resources. Religious rules on fasting, in fact, can be instruments for managing the challenges of food insecurity. This paper analyses different meanings of fasting in religious laws, summarizing the altruistic view that underpins them. Moreover, this matter could be a point of the “strategy of dialogue” that is currently being developed in the EU under the umbrella of the Article 17 of the Treaty on the Functioning of the European Union The ultimate goal is to demonstrate that religious duties can be considered valuable legal resources in achieving global food security. SOMMARIO: 1. Introduction. The right to food in international law: foundations and challenges - 2. The intersection of religious laws and food security: values, authority, and influence - 3. Duties and practices of fasting in different religious legal traditions - 4. Functions of fasting in a globalised scenario: how duties and rights support each other, a) The critical function of the fasting deontology, b) The solidaristic/altruistic function of the fasting deontology - 5. Conclusions.